HAK DAN KEWAJIBAN KARYAWAN: PENERAPAN ETIKA KERJA DALAM MEMBANGUN PROFESIONALISME ALFAMIDI METRO - Intan Aulia Denada; Muhammad Najib Nurkhadziqi, Nova Elisa, Alva Yenica Nandavita (Jurnal Ekonomi dan Bisnis, 2025)
The application of Islamic business ethics and work ethics is the main spearhead for having an attitude of professionalism in fulfilling the rights and obligations of employees within the company. An employee has obligations that must be fulfilled towards the company, so the employee must also get his rights from the company. Professionalism includes attitudes, behavior and work ethics that reflect commitment and responsibility for the tasks carried out by each individual. Therefore, it is hoped that the implementation of work ethics can be the spearhead that enables individuals to uphold their professionalism. The research method used is a qualitative method, namely by conducting direct interviews which are then processed by the author. In the research, the author found that Islamic business ethics which include the principles of monotheism and balance include aspects such as management, professionalism in working in a company or organization which is expected to maintain the company's sustainability.